Suspected colonic cancer turns out to be disseminated tuberculosis in a kidney transplant recipient: A case report. Issue 36 (September 2019) - Schmidt-Lauber, Christian; Jacobi, Johannes; Polifka, Iris; Hilgers, Karl F.; Wiesener, Michael S.
Abstract: Rationale: Active tuberculosis constitutes a relevant risk for kidney transplant recipients. In contrast to immunocompetent hosts, kidney transplant recipients often show atypical presentation and course of the disease impeding diagnosis. Especially extrapulmonary or disseminated infection is more frequent and can resemble malignant processes. However, reactivation of tuberculosis mostly develops within the early post-transplant course, whereas malignancies are predominantly long-term complications. We report a case of disseminated abdominal tuberculosis developing 10 years after kidney transplantation and review the underlying literature. Patient concerns and diagnoses: A 51-year-old lady presented with epigastric pain, diarrhea, weight loss and night sweats 10 years after deceased-donor kidney transplantation. An epigastric as well as multiple peritoneal masses were found suspicious of a cancer of unknown primary. Colonoscopy revealed a colon tumor with the biopsy showing no dysplasia but histiocytic and granulomatous infiltration with acid-fast bacilli. Mycobacterium tuberculosis was detected in the biopsy and stool and disseminated abdominal tuberculosi was diagnosed. Interventions and outcomes: With anti-tuberculosis therapy, the masses regressed, and all cultures became sterile, sparing graft function. Lessons: This case emphasizes how variable and unspecific the presentation of tuberculosis in kidney transplant recipients may be and that tuberculosis constitutes a relevant risk also in the long-term post-transplant course.